Theoretical aspects of speed-strength training of short-distance runners - Buriyevich, B. B. (Proximus Journal of Sports Science and Physical Education, 2024)
Based on a theoretical analysis of data from scientific and methodological literature, the main direction and specific features of the training of qualified short-distance runners were determined. It has been established that the main condition for determining the content of training programs is the selection of the leading components of athletes' preparedness.